Severe Outbreak of a Yellow Mosaic Disease on the Yard Long Bean in Bogor, West Java - TRI ASMIRA DAMAYANTI; OLUFEMI JOSEPH ALABI; RAYAPATI ADIKESAVULU NAIDU; AUNU RAUF (Bogor Agricultural University, Indonesia, 2009)
During 2008 crop season, an outbreak of severe yellow mosaic disease on yard long bean (Vigna unguiculata subsp. Sesquipedalis) occurred in several farmers’ fields in West Java. Yard long bean var. Parade inoculated manually with extracts from symptomatic leaves showed the symptoms indicating the presence of virus. Symptomatic leaf samples tested positive in enzyme linked immunosorbent assay (ELISA) with antibodies to group specific Potyvirus and Cucumber mosaic virus (CMV). Total RNA derived from symptomatic leaves was subjected to reverse transcription-polymerase chain reaction (RT-PCR) using primers specific to the cylindrical inclusion (CI) protein of potyviruses and CMV coat protein (CP) specific primers. Pair wise comparison of sequences obtained from cloned RT-PCR products with corresponding nucleotide sequences in the GenBank confirmed the presence of Bean common mosaic virus strain Blackeye (BCMV-BlC) and CMV in the symptomatic beans. Sequences of BCMV and CMV isolates from the beans showed maximum nucleotide sequence identities (92-97%) and (90%), respectively with BCMV-BIC and CMV isolates from Taiwan. Each virus isolate also clustered closely with corresponding isolates from Taiwan in a phylogenetic analyses. These results provide first evidence of the occurrence of multiple infection of BCMV-BIC and CMV in the yard long been from Bogor, West Java. Key words: yard long bean, BCMV-BIC, CMV, Bogor Indonesia